Cross Word Puzzle Method: Upaya Meningkatkan Minat dan Hasil Belajar IPS di SMP Negeri 1 Krangkeng Indramayu - Rahayu Dewi Iriantiningsih (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2022)
This study aims to analyze the use of cross-word puzzle learning media in increasing student interest and learning outcomes in social studies subjects. This research is an action research conducted in three cycles including planning, implementation, observation, and reflection activities. The subject of the study was a class VIII student at SMP Negeri 1 Krangkeng. The results showed that the average percentage of student interest indicators in the first cycle of 62% increased to 70% in cycle II, it has further increased to 88%. Meanwhile, in the learning outcomes indicator, the average percentage of students who achieve KKM scores in the first cycle of 20% increases to 60% in cycle II. Cross word puzzle learning media can be applied to students in education at the junior secondary level and can improve student learning outcomes and can increase student interest in learning.